Inter-sectoral linkages in Nigeria: evidence from agriculture and manufacturing sectors (2024)
This paper examined the essence of inter-sectoral linkages in the agricultural and manufacturing sectors of Nigeria’s economy using data obtained from the Central Bank of Nigeria (CBN) which covers from 1981 to 2020. The study employed impulse response and variance decomposition functions. The main findings have shown that there is an important bidirectional relationship between the agricultural and manufacturing sectors, intuitively showing that the two sectors in Nigeria have a forward and backward connection. Secondly, agricultural development is a credible input engine for the manufacturing sector, but it has been discovered that the route of impulse from the manufacturing sector to the agricultural sector is inconsistent, which implies that the manufacturing sector can only support the agricultural sector in the short-run. The variance decomposition which shows the shock effect of the linkage clearly showed that a shock in the agricultural sector only results in an 8 percent variation in the manufacturing sector while a shock in the manufacturing sector only explained 9.5 percent variation in agricultural sector. Finally, there is a feedback impact between the agricultural sector and the other sectors in Nigeria which suggests that the agricultural sector is the primary engine of the Nigerian economy. The results lead to an important recommendation that government policies to support agriculture should be encouraged as the dynamic results revealed that agriculture has a significant positive multiplier effect in the economy. Hence, government should encourage the production of more agricultural products that could be used as raw materials in the manufacturing sector.